A Case of Swyer-James-Macleod Syndrome Associated with Middle Lobe Hypoplasia and Arteriovenous Malformation. (9th December 2012) - Kaplanoglu, Hatice; Kaplanoglu, Veysel; Toprak, Ugur; Dilli, Alper; Hekimoglu, Baki
Abstract : A 58-year-old female patient presented to the hospital with hearing loss. In the chest radiography obtained before her ear surgery, volume decrease in the right hemithorax, elevation of the right diaphragm, and increase of ventilation in the right lung were detected. At the thorax CT-CT angiography, hypoplasia of the main pulmonary artery and its branches and arteriovenous malformation localized in the middle lobe of the right lung were detected. Thus, diagnosis of Swyer-James-Macleod syndrome associated with right lung middle lobe hypoplasia and arteriovenous malformation was made. This kind of association has not been reported earlier, so we are presenting it in the light of the literature knowledge.